Neonatal Death in Low- to Middle-Income Countries: A Global Network Study - Belizán, José M.; McClure, Elizabeth M.; Goudar, Shivaprasad S.; Pasha, Omrana; Esamai, Fabian; Patel, Archana; Chomba, Elwyn; Garces, Ana; Wright, Linda L.; Koso-Thomas, Marion; Moore, Janet; Althabe, Fernando; Kodkany, Bhala S.; Sami, Neelofar; Manasyan, Albert; Derman, Richard J.; Liechty, Edward A.; Hibberd, Patricia; Carlo, Waldemar A.; Hambidge, K. Michael; Buekens, Pierre; Jobe, Alan H.; Goldenberg, Robert L. (American Journal of Perinatology, 2012)
Objective To determine population-based neonatal mortality rates in low- and middle-income countries and to examine gestational age, birth weight, and timing of death to assess the potentially preventable neonatal deaths.Methods A prospective observational study was conducted in communities in five low-income countries (Kenya, Zambia, Guatemala, India, and Pakistan) and one middle-income country (Argentina). Over a 2-year period, all pregnant women in the study communities were enrolled by trained study staff and their infants followed to 28 days of age.Results Between October 2009 and March 2011, 153,728 babies were delivered and followed through day 28. Neonatal death rates ranged from 41 per 1000 births in Pakistan to 8 per 1000 in Argentina; 54% of the neonatal deaths were >37 weeks and 46% weighed 2500 g or more. Half the deaths occurred within 24 hours of delivery.Conclusion In our population-based low- and middle-income country registries, the majority of neonatal deaths occurred in babies >37 weeks' gestation and almost half weighed at least 2500 g. Most deaths occurred shortly after birth. With access to better medical care and hospitalization, especially in the intrapartum and early neonatal period, many of these neonatal deaths might be prevented.
Keywords: neonatal mortality; low-income countries; preterm birth